Strategies for Improving the Development of BUMDes in Bangka Regency Towards Dynamic Institutions - Divina Aufa Widiana; Dwi Rizka Zulkia (UPT Publikasi Ilmiah UNISBA, 2024)
The Village SDGs refer to the implementation of the Sustainable Development Goals, a set of global goals set to achieve sustainable development by 2030. Goal 18 of the Village SDGs focuses on the importance of addressing economic inequality and ensuring that economic growth does not only involve a few people but also benefits the entire village community. This goal can be realized by developing Village-Owned Enterprises (BUMDes) that have a strategic role in driving economic development at the village level through engaging and strengthening human resources by encouraging active participation of village communities. This research aims to identify problems in the development of BUMDes and to formulate a BUMDes development plan in accordance with the potential of local resources in villages in Bangka Regency. The research method used is a qualitative descriptive approach using primary and secondary data. The data analysis technique uses SWOT analysis consisting of Strengths, Weaknesses, Opportunities, and Threats. This research shows that there are components that need to be developed to make BUMDes a driver of the village economy, namely strengthening village human resources, establishing an active and responsive organizational structure, and collaboration of various parties including academics that can increase the positive impact on BUMDes.